USM VC IN TALKS ON THE POTENTIAL TO OFFER DENTISTRY AT THE USM-KLE CAMPUS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KARNATAKA, INDIA, 18 November 2016 The ViceChancellor of Universiti Sains Malaysia (USM) Professor Datuk Dr. Asma Ismail yesterday held discussions with the Director of the USMKLE International Medical Programme, Dr. H.B. Rajasekhar as part of her official educational visit to India.